A REFERENCE TEXT OF JOSÉ ANASTÁCIO DA CUNHA: BALISTIQUE ARITHMETIQUE, BY PIERRE-LOUIS DE MAUPERTUIS - Saraiva, Luis (Revista Brasileira de História da Matemática, 2020)
At the beginning of 2005, Maria do Céu Silva, a researcher at the Oporto University Mathematics Centre, came across six unpublished manuscripts by the Portuguese mathematician José Anastácio da Cunha (1744-1787) in the Braga District Archive. A little later a seventh manuscript was discovered in the same archive by Maria Elfrida Ralha, a University of Minho researcher.